2013
DOI: 10.6061/clinics/2013(05)13
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between low maternal serum 25-hydroxyvitamin D levels and gestational diabetes mellitus according to the severity of 25-hydroxyvitamin D deficiency

Abstract: OBJECTIVE:To assess the relationship between low maternal serum 25-hydroxyvitamin D levels and gestational diabetes mellitus in Turkish pregnant women according to the severity of 25-hydroxyvitamin D deficiency and assess intact parathyroid hormone levels in women with gestational diabetes mellitus and controls with low and sufficient 25-hydroxyvitamin D levels.METHODS:We analyzed serum 25-hydroxyvitamin D and intact parathyroid hormone levels in 234 women with gestational diabetes mellitus and 168 controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
2
38
3
1
Order By: Relevance
“…Similar results were reported in a study conducted in Canada (2012) where GDM group had higher BMI than non-GDM group (71.3± 18.4 vs 65.2 ±12.0 p=0.0005) (Parlea et al, 2012). Also in Turkey, the authors reported significant older age and higher BMI among GDM group compared with non-GDM (p=0.002, p<0.001) respectively (Zuhur et al, 2013).…”
Section: Data Are Presented As Mean +/-Sd (Minimum -Maximum)supporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were reported in a study conducted in Canada (2012) where GDM group had higher BMI than non-GDM group (71.3± 18.4 vs 65.2 ±12.0 p=0.0005) (Parlea et al, 2012). Also in Turkey, the authors reported significant older age and higher BMI among GDM group compared with non-GDM (p=0.002, p<0.001) respectively (Zuhur et al, 2013).…”
Section: Data Are Presented As Mean +/-Sd (Minimum -Maximum)supporting
confidence: 78%
“…Parlea et al conducted a nested case-control study among 345 pregnant women (116 GDM & 219 non-GDM) and they reported significant lower vitamin D serum level in GDM group (56.3 vs. 62.0 nmol⁄ l, P = 0.018) (Parlea et al, 2012). Also, in Turkey, Zuhur et al recognized significant increase in GDM cases among women who suffered from severe vitamin D deficiency (Zuhur et al, 2013). All these studies and other studies provided clear evidence of vitamin D being a risk factor in the development of GDM (Parlea et al, 2012).…”
Section: Data Are Presented As Mean +/-Sd (Minimum -Maximum)mentioning
confidence: 99%
“…There was no statistical significance between cases and controls according to parity (p>0.05). This is in contrast with study by Zuhur et al (11) in which the percentage of multipara was 85.9% in women with GDM and 60.7% in controls with significant difference. This difference might be due to difference in the methods used for the diagnosis of GDM.…”
Section: Discussioncontrasting
confidence: 56%
“…It complicates two to five percent of pregnancies, of which 90% is contributed by gestational diabetes mellitus (GDM) (11) . The controversy and confusion still exists because of various guidelines for diagnosis of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zuhur et al (19) studied 234 cases of GDM and 168 controls in Turkey and reported that only severely deficient maternal serum 25(OH)D levels (<5.2 ng/mL) were significantly associated with an elevated relative risk of GDM. Likewise, Maghbooli et al (11) studied maternal vitamin D deficiency and GDM in a cross-sectional study of 741 pregnant women at 24-28-weeks gestation and found significantly lower levels of 25(OH)D in women with GDM compared to normoglycaemic controls.…”
Section: Discussionmentioning
confidence: 99%